Pemanfaatan metode Pose to Pose dalam pembuatan animasi 3D Islami ‘Beli Sepatu’ untuk mengungkap nilai- nilai Islami - Raidah, Afiifah Zain; Nugroho, Fresy; Fadila, Juniardi Nur (Maliki Interdisciplinary Journal, 2024)
This research examines the use of the pose-to-pose method in the design of Islamic 3D animation titled "Beli Sepatu". The aim is to apply the pose-to-pose technique in creating Islamic 3D animations. This method prioritizes planning key poses to produce smooth and expressive animations. The study involves three stages: pre-production, production, and post-production. Key poses serve as the animator’s reference in building the animation as a whole. Implementation is carried out using Blender. The research findings indicate that employing the pose-to-pose method in the Islamic 3D animation "Beli Sepatu" results in a smooth, expressive animation capable of conveying Islamic messages. This method provides a systematic framework and assists animators in efficiently organizing character movements. The research holds importance in delivering high-quality Islamic 3D animations that inspire and educate, utilizing appropriate design techniques. Therefore, this study recommends the use of the pose-to-pose method in Islamic 3D animation design to achieve superior results and effectively communicate Islamic messages.